VD_FINDINFO Arrêt / 2018 / 421 vom 18. Mai 2018 - VD Tribunal cantonal (2018)
CURATELLE DE PORTÉE GÉNÉRALE, PLACEMENT À DES FINS D'ASSISTANCE, PROPORTIONNALITÉ, SUBSIDIARITÉ | 390 al. 1 ch. 1 CC, 398 CC, 450 CC